RETROSPECTIVE ANALYSIS OF MENSTRUAL-OVARIAN FUNCTION DISORDERS IN WOMEN WITH COVID-19 - Yuldasheva, N.Z. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Background. Disorders of menstrual-ovarian function in women with COVID-19 are an urgent problem since they can lead to further diseases of the reproductive system and complications of pregnancy. The purpose of this study is to conduct a retrospective analysis of menstrual-ovarian function disorders in women who have had COVID-19. Materials. A retrospective analysis of the medical records of 100 women who were hospitalized with a diagnosis of COVID-19 in the period from January 2020 to January 2021 with menstrual-ovarian function disorders was carried out. Of these, 65 women (65%) were aged from 18 to 30 years, 25 women (25%) - from 31 to 35 years and 10 women (10%) from 36 to 40 years. The average age of the women in the study was 28±0.4 years. Results. When analyzing the relationship between the severity of COVID-19 disease and menstrual-ovarian function disorders, a statistically significant inverse correlation was revealed (r=-0.45, p<0.01). That is, the more severe the COVID-19 disease was, the higher the risk of developing menstrual-ovarian function disorders. There was also a statistically significant relationship between the duration of COVID-19 disease and disorders of menstrual-ovarian function (p<0.05). Women who were ill for more than 4 weeks had a higher risk of developing menstrual-ovarian function disorders. Multiple regression showed that the severity of COVID-19 disease and the duration of the disease are independent factors affecting menstrual-ovarian function disorders. Conclusion. A retrospective analysis of menstrual-ovarian function disorders in women with COVID-19 confirms the potential impact of coronavirus on menstrual-ovarian function. The following types of menstrual-ovarian function disorders were identified in the women included in the study: amenorrhea in 17%, oligomenorrhea in -21%, dysmenorrhea in 17% and abnormal uterine bleeding in 45% of patients. The average duration of violations was 3.8 months. The results of a retrospective analysis showed that women who have had COVID-19 have a high risk of developing menstrual-ovarian function disorders. A more severe and prolonged COVID-19 disease increases this risk by 2.5 times.